2005
DOI: 10.1111/j.1600-0463.2005.apm1130101.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of five essential oils against origin strains of the Enterobacteriaceae family

Abstract: An in vitro assay measuring the antimicrobial activity of essential oils of Coridothymus capitatus (Spanish origanum), Satureja montana, Thymus mastichina (Spanish Origanum majorana), Thymus zygis (Spanish variety of Thymus vulgaris) and Origanum vulgare has been carried out against poultry origin strains of Escherichia coli, Salmonella enteritidis and Salmonella essen, and pig origin strains of enterotoxigenic E. coli (ETEC), Salmonella choleraesuis and Salmonella typhimurium. Using the broth microdilution me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 3 publications
11
98
1
6
Order By: Relevance
“…As a sole component, thymol was already presented as a good antimicrobial agent in several studies (Penalver et al, 2005;Sokovic et al, 2008Sokovic et al, , 2009. On the other hand, although the lowest thymol content among the three thyme EOs, the oil of T. serpyllum exhibited the strongest activity, implying that, although the thymol is the major oil constituent, obviously it is not the only one responsible for achieved good antimicrobial activity; the involvement of less abundant constituents should also be considered.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…As a sole component, thymol was already presented as a good antimicrobial agent in several studies (Penalver et al, 2005;Sokovic et al, 2008Sokovic et al, , 2009. On the other hand, although the lowest thymol content among the three thyme EOs, the oil of T. serpyllum exhibited the strongest activity, implying that, although the thymol is the major oil constituent, obviously it is not the only one responsible for achieved good antimicrobial activity; the involvement of less abundant constituents should also be considered.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Their efficiency against a large variety of pathogens and food-borne germs has been proven by recent investigations [11,13,14]. Several of the studies [1,15,16] indicated the sensitivity of Gram-positive bacteria, while others [17][18][19] have shown expressed sensitivity of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the main component in other species of Eucalyptus can be a different compound, such as piperitone (E. dives), (E)-methyl cinnamate (E. olida) (Gilles et al, 2010), α-pinene (E. camaldulensis) (Cheng et al, 2009), limonene (E. staigeriana), β-citronellal (E. citriodora) (Maciel et al, 2010), or p-cymene (E. tereticorni) (Toloza et al, 2006). The chemical composition of essential oil is affected by several factors, such as species, geographical location, harvest time, plant part and isolation method (Cimanga et al, 2002;Penalver et al, 2005;Marzoug et al, 2011).…”
Section: Discussionmentioning
confidence: 99%